Peningkatan Minat Belajar Siswa Melalui Pendekatan Problem Based Learning Pada Mata Pelajaran Matematika Kelas II SDN Bawuran - Ulfah Azizah (Publikasi Indonesia, 2022)
The low interest in learning of grade II students at SDN Bawuran encouraged researchers to conduct class action research at SDN Bawuran. This study aims to (1) know the implementation of learning using the Problem Based Learning approach as an effort to increase students' learning interest in grade II mathematics subjects at SDN Bawuran, and (2) increase students' learning interest in grade II mathematics subjects at SDN Bawuran using the Problem Based Learning approach. The research method used is class action research, Kemmis &Taggart model. The subjects of this study were 23 grade II students of SD N Bawuran. The research was conducted in two cycles. Each cycle consists of two meetings. Research in an effort to increase students' learning interest through PBL in grade II mathematics subjects sdn Bawuran has been conducted with the results can increase students' learning interest, it is shown the initial condition of the average learning interest score of 61 (less interested) with a percentage of the number of students at least less interested 56%; Cycle 1 is 66 (quite interested) with a percentage of 65%; Cycle 2 is 73 (quite interested) with a percentage of 82%.